2011
DOI: 10.1371/journal.pone.0025811
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning with Physiological Levels of Ethanol Protect Kidney against Ischemia/Reperfusion Injury by Modulating Oxidative Stress

Abstract: BackgroundOxidative stress due to excessive production of reactive oxygen species (ROS) and subsequent lipid peroxidation plays a critical role in renal ischemia/reperfusion (IR) injury. The purpose of current study is to demonstrate the effect of antecedent ethanol exposure on IR-induced renal injury by modulation of oxidative stress.Materials and MethodsBilateral renal warm IR was induced in male C57BL/6 mice after ethanol or saline administration. Blood ethanol concentration, kidney function, histological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
4
32
1
Order By: Relevance
“…Of these, the excessive generation of ROS causes damage and death of renal tubular epithelial cells [7]. The role of ROS in the pathophysiology of I/R injury is supported by increased formation of lipid peroxidation and other toxic products following renal injury [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Of these, the excessive generation of ROS causes damage and death of renal tubular epithelial cells [7]. The role of ROS in the pathophysiology of I/R injury is supported by increased formation of lipid peroxidation and other toxic products following renal injury [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is associated with mitochondrial dysfunction and impaired oxygen consumption (16,17), ALDH2 is localized in the mitochondrial fraction, and mitochondrial dysfunction changes ALDH2 function. A number of studies have reported that ALDH2 protects against organ injury, such as that affecting the kidneys, heart and neurons (10,(18)(19)(20). Our previous studies showed that cardiac ALDH2 expression was decreased in rats with diabetes, or myocardial ischemia and reperfusion injury, and that upregulation of ALDH2 protected against myocardial injury and protected the lungs against diabetes-induced lung injury, all of which indicate that ALDH2 could be an intrinsic factor regulating the occurrence of disease (12,21,22).…”
Section: Discussionmentioning
confidence: 91%
“…With regard to the role of ALDH2 in the pathogenesis of sepsis, Chen et al reported that hepatic ALDH2 activity was downregulated in septic rats following cecal ligation and puncture (CLP) (9). It has been reported that preconditioning with ethanol to stimulate ALDH2 activity prevented kidney ischemia and reperfusion injury in mice (10); however, the role of renal ALDH2 in sepsis-induced AKI is unclear. It remains to be determined whether ALDH2 is also a key factor associated with kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a study performed on mice showed that moderate antecedent ethanol exposure provides protection for the kidneys against subsequent IR-induced injury 17 . In contrast, ethanol (1.9%) was shown to have a tendency to increase superoxide anion production in a model of cold preservation-warm reperfusion liver injury and this effect was detected to be reversed by the application of silibinin in a previous study 5 .…”
Section: Resultsmentioning
confidence: 99%